Aerosols in dental clinics, increased risk concern of SARS-CoV-2 related infection - Esperanza Caridad León-Betancourt (Centro Editorial Ciencias Médicas: CPICM Guantánamo, 2021)
Introduction: the use of aerosols in dental clinics represents a very important risk factor to be in focus as they could resulting in bacterial transmission to healthcare workers and entity environment through the dispersion of tiny droplets. Its use, in the presence of COVID-19 pandemic, represents a danger to human life.